Scherzos benjyosos - Sutherland, Keston (The Last Books, 2020)
"Scherzos Benjyosos is a set of four poems, scherzos in prosimetrical blocks, a comical, wild, and delirious sifting through the carnage of the financial crash, the dreamscapes of capitalist infancy, histories of sadism and persecution, the fetish bars of canonical literature, and the psychoanalysis of grass. The book also includes "Sinking Feeling," Sutherland's long poem from 2017, described by J. H. Prynne as "breathtakingly lovely, and desperate, racked with desire to become truthful love.""--Publisher information